Resorcinol Compounds Isolated form the Bark of Myristica fatua Houtt. - Megawati, Megawati; Darmawan, ahmad (Indonesian Journal of Pharmacy, 2017)
Myristica fatua Houtt. is one of the endemic plants growth in Wallace region. Isolation of the secondary metabolite compounds from the ethyl acetate fraction of the bark of Myristica fatua Houtt. has been done using some chromatography techniques afforded two resorcinol compounds, malabaricone C (1),Â  and malabaricone B (2). The structures of 1-2 were determined using spectroscopic techniques, including mass spectrometry, 1D-NMR and 2D-NMR. Both compounds showed in vitro cytotoxic activity against the breast carcinoma cancer cell lines MCF-7 using alamar blue assay method, with IC50 of 2.38 and 0.71 Î¼g/mL, respectively.Â